Designing History-Based Educational Games to Improve Cognitive Empathy in Children with ASD: A Pilot Study - Cai Gi; Nanang Hoesen Hidroes Abbrori (Universitas Islam Kuantan Singingi, 2025)
Children with Autism Spectrum Disorder (ASD) face significant challenges in Theory of Mind (ToM), particularly in understanding others' perspectives. While serious games have shown potential, most existing interventions focus on basic emotion recognition without engaging narrative contexts. Objective: This pilot study aims to design a history-based serious game,